‘Yet his silence said volumes’: a pragmatic analysis of conversational silence in rapport management - Baoqin Wu; Muhammad Afzaal; Dina Abdel Salam El-Dakhs (Cogent Arts & Humanities)
Silences are crucial in interpersonal communication, serving as essential components of interpersonal relationships. The current study utilizes naturally occurring linguistic data and draws upon Spencer-Oatey’s Rapport Management Theory to examine the pragmatic functions of conversational silence in the context of rapport management. The findings reveal that within the framework of rapport orientation, silence plays a pivotal role and can be categorized into four fundamental types: rapport maintenance, rapport neglect, rapport challenge and rapport destruction. The results indicate that the interpretation of silence extends beyond a simplistic and negative process of withholding meaning; rather, it involves a multifaceted method of constructing meaning. As a non-discursive practice, silence can maintain harmonious relationships, avoid controversy, and even trigger conflicts.